The spectrum of unhealthy drug use and quality of care for hypertension and diabetes: a longitudinal cohort study. Issue 12 (21st December 2015) - Kim, Theresa W; Samet, Jeffrey H; Cheng, Debbie M; Bernstein, Judith; Wang, Na; German, Jacqueline; Saitz, Richard
Abstract : Objectives: Although it is well known that addiction is associated with adverse medical consequences, the effects of the spectrum of unhealthy drug use (illicit drug or prescription misuse) on chronic conditions such as hypertension and diabetes are understudied. This study evaluated the associations between measures of drug use (ie, frequency, severity and type) and standard quality metrics for inadequate blood pressure (BP) and blood glucose (BG) control. Design: Longitudinal cohort study. Participants: Adult primary care patients with unhealthy drug use and hypertension or diabetes. Setting: Urban hospital-based primary care practice. Measurements: Outcomes were (1) inadequate BP (systolic BP ≥140 or diastolic BP ≥90) and (2) inadequate BG (glycated haemoglobin ≥8%) control (Healthcare Effectiveness Data and Information Set criteria). Drug use was characterised by a primary independent variable, drug use frequency, and two secondary variables, severity of use and drug type. We fit separate regression models for each drug use measure and outcome. Results: Overall, 40% (65/164) of the sample with hypertension had inadequate BP control and 44% (24/54) of those with diabetes had inadequate BG control. More frequent drug use was not significantly associated with inadequate BP control (adjusted OR (AOR) 0.67; 95% CI 0.31 to 1.46, highest vs lowest tertile; AOR 0.72; 95% CI 0.36 to 1.41, middle vs lowest tertile) or BG control (AOR 0.27; 95% CI 0.07 to 1.10, highest vs lowest tertile; AOR 1.01; 95% CI 0.38 to 2.69, middle vs lowest tertile). Drug use severity was also not associated with BP or BG control. Cocaine use was associated with inadequate BG control compared to marijuana use (AOR 8.82; 95% CI1.86 to 41.90). Conclusions: Among primary care patients with recent drug use and hypertension or diabetes, drug type was significantly associated with inadequate BG, but not BP control. Frequency and severity of use were not significant predictors of either outcome.